2019
DOI: 10.1002/tal.1654
|View full text |Cite
|
Sign up to set email alerts
|

A study on the accuracy of force analogy method in nonlinear static analysis

Abstract: Summary In this paper, the accuracy of the force analogy method (FAM) for nonlinear static (pushover) analysis is investigated. Hence, after explanation of the concept of FAM by a new approach, 12 2D steel special moment resisting frames with different configurations were derived from two different 3D archetypes and modeled using four various methods of capturing nonlinearity including SAP2000 super elements, OpenSees force‐based and displacement‐based fiber method, and FAM. In addition, a MATLAB code was deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…This equation is obtained by limiting the bending moment values using the cross-section capacity functions. Moreover, the bending moment m(t) is calculated using Equation (6).…”
Section: Force Analogy Methods Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…This equation is obtained by limiting the bending moment values using the cross-section capacity functions. Moreover, the bending moment m(t) is calculated using Equation (6).…”
Section: Force Analogy Methods Theoretical Backgroundmentioning
confidence: 99%
“…Coupling FAM with an explicit solver to integrate the equation of motion has proved to be both accurate and numerically efficient not only for regular problems of obtaining the nonlinear structural response of isolated structures [4] but also in the more complex case of structural pounding due to earthquake action [5]. In recent papers, Safaei S. et al [6] studied the accuracy of the FAM for nonlinear static analysis. They concluded that the results are in good agreement with those obtained by other analysis techniques commonly used for seismic performance assessment of structures.…”
Section: Introductionmentioning
confidence: 99%